The impact of three months of adjuvant yoga intervention on glycemic control among adolescents with type 1 diabetes: a randomized control trial - Sonu Maurya; Suchitra Patil; Amit Singh; Indu Rani; Navneet Kaur; Sriloy Mohanty; Akshay Anand; Raghuram Nagarathna (Diabetology & Metabolic Syndrome)
Abstract Background There is growing evidence that shows the benefits of yoga on people with diabetes. The benefit of yoga for people with Type 2 Diabetes has been proven. Incorporating yoga in daily life helps to attain glycaemic control and reduces the risk of complications in people with diabetes especially in the Type 2 Diabetes Mellitus (T2DM) field. However, limited work is done for yoga on Type 1 Diabetes Mellitus (T1DM). The current trial aimed to investigate the effect of yoga intervention on glycemic control and Quality of Life (QoL) among adolescents with T1DM. Methods In this trial, 92 T1DM subjects with mean age of 13.35 ± 2.41 years were recruited and randomly allocated to either yoga or control arm with an allocation ratio of 1:1. The control arm received standard care whereas; the yoga arm received additional tailored yoga sessions for three months. Venous blood samples were collected for HbA1c and average blood glucose (ABG) along with daily insulin requirements, PedsQL-3.0, PedsQL-4.0, Kutcher Adolescent Depression Scale, Fear of hypoglycaemia questionnaire at baseline and post-intervention. Both per-protocol and Intention-to-treat (ITT) analysis were done. Results Out of 92 participants recruited, only 46 could complete the trial (yoga arm: n = 25). The per-protocol analysis showed a significant reduction in the HbA1c levels (14.68% vs. -12.90%;p < 0.001) as well as in the ABG levels (17.72% vs. -15.65%;p < 0.001) in the intervention arm when compared to the control arm. An ITT analysis of the primary objectives also yielded similar results. Further, Insulin requirements (p = 0.04) and hyperglycaemia frequency (p = 0.02) were significantly reduced in the yoga arm however, it lacked significance in between-group analysis. Fear of hypoglycaemia was reduced by 23.9% in the intervention group while it was 3% in the control group which was significant. Significant improvement in QoL, depression, and level of physical activity were observed following yoga intervention compared to the control group. Conclusion The three-month adjuvant yoga intervention was associated with an improved glycaemic control and QoL among adolescents with T1DM.